Thermoluminescent dosimetry properties of double doped calcium tetraborate (CaB4O7:Cu-Mn) nanophosphor exposed to gamma radiation - Haghiri, Maryam Erfani; Saion, Elias; Soltani, Nayereh; Wan Abdullah, Wan Saffiey; Navasery, Manizheh; Ebrahim Saraee, Khadijeh Rezaee; Deyhimi, Najmeh (Elsevier, 2014)
This study reports the dosimeteric properties of double Cu–Mn doped calcium tetraborate nanophosphor prepared by co-precipitation technique. The structure and the morphology of the synthesized nanocrystals were characterized by X-ray diffraction and transmission electron microscope. The presented XRD patterns showed the monoclinic structure and transmission electron microscopy revealed the formation of spherical shape nanoparticles with an average particle size of 8 nm. The results demonstrated that the synthesized calcium borate nanophosphor has the highest dosimetric sensitivity at combined concentration of 2% and 1%, copper and manganese molar ratio, respectively. TL glow curve of this material showed two well resolved peaks located at around 124 and 256 °C. The most striking dosimeteric feature of this nanomaterial is the linearity response, which has a long range of 0.05–3000 Gy for both temperature peaks.